Analisis Konjoin Sebagai Preferensi Konsumen Terhadap Atribut Produk Parfum Mobil Artfresh - Artanti, Damara; Dewi, Yuli Kartika (PERFORMA, 2023)
Artfresh is a business that runs in car perfume field. Artfresh was established in 2018. Artfresh does development car perfume products. The problem that is found in this research is which combination of attributes that become consumer's preference in choosing Artfresh products. The preferences that are measured in this research include smell, use method and material. The population in this research is followers of Instagram Artfresh social media. The type of research that is used in this research is quantitative. Sampling technique in this research is non probability sampling technique. This research uses the sample of 223 respondents by using Slovin formula. Data collection is gathered by distributing online questionnaires. This research uses conjoint analysis. In this research, there are three attributes that become research variables, that is, smell, material and use method. The results of the research show that the attributes that become consumers' preferences in choosing Artfresh car perfume products are smell with important value of 67,999%, then is followed by use method with important value of 18,544% and the last material with important value of 13,456%. The combination of attributes that become consumers’ preferences is the smell of lavender perfume, use method hanged and paper material.